Ground Water Quality (pH) Under Different Vegetative Covers at Osamund (Nilgiri Hills) - Mathur, H. N.; Raj, S. Francis Hilary; Naithan, Sanjay (Indian Forester, 1984)
Groundwater is one of the important sources of water supply and vegetation plays its role in maintaining the quality and quantity of groundwater. However, little data is available in our country on the quality and quantity of groundwater resources as affected by vegetative. Of the many qualities of groundwater, pH measarements under different vegetative cavers was taken for studies Groundwater samples were collected at-fortnightly intervals for two years from piezemetic wells existing in three vegeative covers viz. Eucalyptus plantation, Shola forest and grassland, the samples were analysed for pH. The study indicated no adverse effect on pH of groundwater due to different vegetal covers. However, there is noticeable seasonal variation in pH values of groundwater in the rainy season (pH 5.60) the groundnater becomes more acidic than it is in the dry season (pH 6.52).